A Descriptive Linguistics Analysis on Student’s Essay Writing - Ledy Nurlely (Journal of English Language Studies, 2017)
The objective of this research is to identify student’s abilities and difficulties in writing descriptive essay. This research used qualitative method by descriptive linguistic analysis. The source of the data was taken from one of student’s essay. The finding showed that the student was able to arrange the content using chronological order. He was also capable in applying organization of the content (form). Nevertheless, he still had difficulties in using English grammar. Besides, the student lacked of vocabulary and made little mistake in using capitalization.Keywords: content, form essay, grammar, vocabulary.